PENGARUH MOTIVASI WIRAUSAHA DAN MENTAL WIRAUSAHA TERHADAP JIWA KEWIRAUSAHAAN PADA SISWA/SISWI SEKOLAH MENENGAH KEJURUAN KOTA BOGOR - Engkas Alnopri; Sri Harini (Jurnal Visionida, 2016)
This research is conducted to determine the condition of entrepreneurial motivation and entrepreneurial mental to entrepreneurial spirit in Vocational High School students at Bogor city and its influence. The population research is the eleventh grade students fromVocational High School (SMK) in Bogor city and it uses quantitative descriptive method. 100 samples are taken from 17,908 populations. The samplings use purposive and probability stratified random sampling technique. The results of the study show that the condition entrepreneurial motivation of students is high enough, the mental condition of the student is strong enough and they have good condition in entrepreneurial spirit. Entrepreneurial motivation and entrepreneurial mental variabel have a positive effect to the entrepreneurial spirit variabel partially with t-count equal to 6.335 for entrepreneurial motivation variable and 2.711 for the entrepreneurial mental variabel, with a t-table 1.661 and simultaneously with the F-count 116.077 and F-table 3.09. For the results of the analysis of the correlation coefficient is equal to 0.840 which means it has a very strong relationship. While the results of the coefficient correlation analysis are obtained a value of 0.705 which means that the influence of the independent variable on the dependent variable is 70.5% and 29.5% remain is influenced by other factors outside the research. Keywords : Entrepreneurial Motivation, Entrepreneurial Mental, Entrepreneurial Spirit